Signaling Pathway of Nucleotide-Binding Oligomerization Domain-Containing Protein 1 and Potential Therapeutic Targets for Regulating the Gut Microbiota of Individuals with Gallstone Disease - Sanjana Murali; Nandini Krishnamurthy; R. B. Devi Krishna; Shanthi Vijayaraghavan; S. Rajesh Kumar; Andrea Mary Francis (Journal of Bio-X Research)
Gallstone disease (GD) poses a substantial health challenge worldwide, and its complications are often associated with disturbances in the gut microbiota. The essential receptor through which the innate immune system detects bacterial components and controls inflammation, namely, nucleotide-binding oligomerization domain-containing protein 1 (NOD1), is a major participant in the interaction. This article examines the role of NOD1 in GD, focusing on how gallstone-induced changes in the gut microbiota composition activate NOD1. Such activation initiates signaling pathways that lead to gut dysbiosis, further exacerbating GD. We investigate potential therapeutic targets within the NOD1 signaling pathway and its interactions with other host factors, suggesting methods to restore imbalances in the gut microbiota and improve GD management. The clinical significance of these findings and future research directions are also discussed, highlighting the importance of comprehensive approaches to treat GD by targeting NOD1 activity and the gut microbiota.